An Analysis of the Formation of Sub holdings in State-Owned Enterprises - Meilina, Namira; Yani, Teuku Ahmad; M. Jafar (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
The formation of subholdings as part of the restructuring of State-Owned Enterprises (BUMN) aims to improve efficiency and increase company value through functional specialization, as well as to enhance global competitiveness. However, Indonesian positive law does not yet provide clear and detailed regulation regarding the legal status of BUMN subholdings. This legal uncertainty creates issues related to state capital ownership status, the extent of parent company liability, and the independence of the subholding’s board of directors. This study aims to analyze the legal relationship between the parent company and subholding within the BUMN structure, the responsibility of BUMN as the state mandate holder in forming subholdings, and the legal limitations of parent company control from a corporate law perspective. The research uses a normative legal method with statutory and conceptual approaches based on secondary data, which are analyzed qualitatively. The results show that the relationship between the parent company and subholding after Government Regulation No. 72 of 2016 is purely civil. Subholding is a separate legal entity under company law and is no longer categorized as a BUMN. Its assets are separated from state assets, while excessive control may trigger piercing the corporate veil.